Estimation of a term structure model of carbon prices through state spaces methods: a pitch. Issue 1 (9th December 2020) - Aspinall, Thomas William; Gepp, Adrian; Harris, Geoff; Kelly, Simone; Southam, Colette; Vanstone, Bruce
Abstract : Purpose: The pitching research template (PRT) is designed to help pitchers identify the core elements that form the framework of any research project. This paper aims to provide a brief commentary on an application of the PRT to pitch an environmental finance research topic with a personal reflection on the pitch exercise discussed. Design/methodology/approach: This paper applies the PRT developed by Faff (2015, 2019) to a research project on estimating the strength of carbon pricing signals under the European Union Emissions Trading Scheme. Findings: The PRT is found to be a valuable tool to refine broad ideas into impactful and novel research contributions. The PRT is recommended for use by all academics regardless of field and particularly PhD students to structure and communicate their research ideas. The PRT is found to be particularly well suited to pitch replication studies, as it effectively summarizes both the "idea" and proposed "twist" of a replication study. Originality/value: This letter is a reflection on a research teams experience with applying the PRT to pitch a replication study at the 2020 Accounting and Finance Association of Australia and New Zealand event. This event focused on replicable research and was a unique opportunity for research teams to pitch their replication research ideas.